Inflammatory Basis of Pulmonary Arterial Hypertension: Implications for Perioperative and Critical Care Medicine. (October 2019) - Goldenberg, Neil M.; Rabinovitch, Marlene; Steinberg, Benjamin E.
Abstract : Patients with pulmonary arterial hypertension have exceptionally high perioperative risk. This review summarizes the clinical presentation and therapies for pulmonary arterial hypertension, and it highlights evidence for inflammation as a driver of disease pathogenesis and a therapeutic target.